Preparation of Composite Preservation Paper Containing Antagonistic Fungi and Its Application on Apple Preservation - Yixuan LIU; Hong YUE; Xinyu SI; Menghan ZHOU; Cunkun CHEN; Honglian GUO (Shipin gongye ke-ji)
In order to study the properties of composite preservation paper containing antagonistic fungi and the effect of the composite preservation paper on the physiological quality and preservation quality of Gala apples at room temperature, and at the same time to solve the limitations of the antagonistic fungi in the application of difficult to germinate, subject to the influence of the environment, etc., this study used Pichia membranaefaciens as the antagonistic fungi, added to the mixture of 1.16% gelatin and 2% trehalose solution, and combined with a paper-based material to prepare a composite preservation paper containing antagonistic fungi. The structure was characterized, and the physical properties and thermal stability performance of the composite preservation paper were measured. Effects of composite preservation on the natural disease incidence of Gala apples, spot diameter, weight loss, hardness, browning degree, reducing sugar, titratable acid, vitamin C and soluble solids content were analyzed to comprehensively evaluate the preservation effect of the composite preservation paper on Gala apples. Results showed that the composite preservation liquid containing antagonistic fungi caused the surface of Alternaria spp. spores to crumple and deform, and the morphology was destroyed. The composite preservation liquid containing antagonistic fungi at a concentration of 108 CFU/mL was tightly combined with the paper-based material. The water absorption rate of the composite preservation paper was 768.94%±38.05%, which was at a high level. The thickness of the composite preservation paper was 0.232±0.008 mm, the tensile strength was 13.88±0.59 N/mm2, and the percentage of breaking elongation was 6.33%±0.58%, indicating that it had good physical properties. There was a major mass loss in the range of 320~450 ℃, and the residual rate was 5.31% at 800 ℃, with good thermal stability. In vivo application showed that the composite preservation paper could effectively delay the expansion of spots in inoculated fruits, reduce the weight loss rate and browning degree of fruits and maintain the hardness of fruits, delay the reduction of vitamin C, reducing sugar and soluble solids content of fruits, maintain the good organoleptic and physiological qualities of fruits, and prolong the storage time. The composite preservation paper has good physical properties and thermal stability, and maintains the storage quality of Gala apples after harvesting, which not only provides new ideas for antagonistic yeast inhibition and preservation, but also provides a reference for the development of new biological preservation paper and preservation application.